(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2016)
The combination of furosemide (furo) and spironolactone (spiro) is very effective in the treatment of heart failure. In that case, maintaining good quality of these drugs in commercial tablets is must. Therefore, a simple, economical, precise and accurate method, i.e; chemometric assisted UV spectroscopy, for simultaneous determination of furosemide and spironolactone in combined dosage form has been developed. In this study, principal component regression (PCR) has been reported for this purpose. A calibration set of 36 mixture solutions containing furosemide and spironolactone in methanol in the concentration range of 2.0-12.0 ?g/ml and 5.0-30.0 ?g/ml respectively has been prepared by means of an orthogonal experimental design. The absorbance data for the concentration set have been obtained by direct measurement in UV spectrophotometer at 101 wavelength points in the spectral region of 200-300 nm for the zero order spectra. The chemometric technique is also successfully applied to available pharmaceutical formulations, tablets, with no interference from excipients. The analytical performances of principal component regression are characterized by relative prediction errors and recoveries (%). The good recoveries obtained in this case proved that the proposed chemometric technique could be applied efficiently in the quality control of the studied drugs simultaneously in their mixture as well as in the commercial dosage form with satisfactory precision and accuracy as alternative analysis tools. Bangladesh J. Sci. Ind. Res. 51(4), 297-306, 2016